1989
DOI: 10.1128/jb.171.11.5995-6004.1989
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the oxygen-dependent promoter of the Vitreoscilla hemoglobin gene in Escherichia coli

Abstract: The gene coding for the VitreoscUla hemoglobin (VHb) molecule has been cloned and functionally expressed in Escherichia coli. By using a plasmid-encoded gene as well as single-copy integrants, the oxygen-dependent VHb gene (VHb) promoter was shown to be functional in E. coli. The promoter was maximally induced under microaerobic conditions (dissolved oxygen levels of less than 2% air saturation). Direct analysis of mRNA levels as well as the use of gene fusions with lacZ showed that oxygen-dependent regulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(67 citation statements)
references
References 43 publications
5
62
0
Order By: Relevance
“…After the cloning of the VHb gene ( vgb ), VHb was expressed in a number of heterologous bacterial and eukaryotic hosts, where, in general, it was associated with enhanced growth. In its native host, as well as several of the heterologous hosts, VHb production is induced under conditions of low oxygen or hypoxic conditions [Boerman and Webster, 1982;Dikshit et al, 1990;Joshi and Dikshit, 1994;Khosla and Bailey, 1989;Tsai et al, 1995b;Yang et al, 2005]. Transformation of Escherichia coli with vgb was particularly simple because of the extensive knowledge of the genetics, molecular biology, and biochemistry in this organism.…”
Section: Introductionmentioning
confidence: 99%
“…After the cloning of the VHb gene ( vgb ), VHb was expressed in a number of heterologous bacterial and eukaryotic hosts, where, in general, it was associated with enhanced growth. In its native host, as well as several of the heterologous hosts, VHb production is induced under conditions of low oxygen or hypoxic conditions [Boerman and Webster, 1982;Dikshit et al, 1990;Joshi and Dikshit, 1994;Khosla and Bailey, 1989;Tsai et al, 1995b;Yang et al, 2005]. Transformation of Escherichia coli with vgb was particularly simple because of the extensive knowledge of the genetics, molecular biology, and biochemistry in this organism.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription of the hemoglobin from the aerobic bacterium Vitreoscilla is elevated under oxygen-limiting conditions (6,7). Heterologous overexpression of the Vitreoscilla globin allows growth to higher cell densities in Escherichia coli and nearly doubles the growth rate of transgenic tobacco, suggesting an ability to increase the availability of intracellular oxygen (8,9).…”
mentioning
confidence: 99%
“…The evolutionary and functional significance of VHb in existing as single-domain hemoglobin and its implication in Vitreoscilla cellular metabolism remains unclear. In the strictly aerobic bacterium Vitreoscilla sp., expression of the vgb gene is strongly induced by a decrease in oxygen level (8,9,26). Extensive biochemical and genetic studies on VHb have suggested that it facilitates oxygen delivery to the respiratory apparatus of its host (45) and thus enhances its growth metabolism (25,27) or that it may act as an alternative terminal oxidase itself (10).…”
mentioning
confidence: 99%